Pengaruh Good Corporate Governance, Kinerja Keuangan, Dan Kebijakan Keuangan Terhadap Nilai Perusahaan (Pada Perusahaan Go Public Yang Masuk Dalam Penilaian Cgpi Tahun 2006-2013) - Indriastuti, Yuliana, Dr. Triyono, SE, M.Si (2016)
The purpose of this study was to test the effect of good corporate governance proxy for corporate governance perception index, financial performance proxy for profitabillitas, liquidity, and activity and financial policy proxy for debt policy and dividend policy on firm value as measured by Tobin's Q. The population in this study is a company registered in the assessment of corporate governance perception index in 2006-2013. The sample is determined by purposive sampling technique. The hypothesis test uses multiple linear regression analysis. The results showed that the profitability, liquidity, activity affect the value of the company. While corporate governance perception index, debt policy and dividend policy does not affect the value of the company.